Synthetic Aperture Radar Signal Processing using GPGPU - Denham, Mónica (2014)
In this work an effcient parallel implementation of the Chirp Scaling Algorithm (CSA) for Synthetic Aperture Radar (SAR) processing is presented. The architecture selected for the implementation is General Purpose Graphic Processing Unit (GPGPU), as it is well suited for scientific applications and real time implementation of algorithms. The analysis of a first implementation led to several improvements which resulted in an important final speedup. Details of the issues found are explained, and the performance improvement of their correction explicitly shown.